2020
DOI: 10.1007/s10393-020-01503-x
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Coronaviruses or Other Potentially Zoonotic Viruses in Sunda pangolins (Manis javanica) Entering the Wildlife Trade via Malaysia

Abstract: The legal and illegal trade in wildlife for food, medicine and other products is a globally significant threat to biodiversity that is also responsible for the emergence of pathogens that threaten human and livestock health and our global economy. Trade in wildlife likely played a role in the origin of COVID-19, and viruses closely related to SARS-CoV-2 have been identified in bats and pangolins, both traded widely. To investigate the possible role of pangolins as a source of potential zoonoses, we collected t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 37 publications
(45 reference statements)
0
56
0
Order By: Relevance
“…The most common routes involve moving the animals from Southeast Asia (Myanmar, Malaysia, Laos, Indonesia, Vietnam) to Guangxi, Guangdong, and Yunnan. The most likely scenario is that these Sarbecoviruses infected the pangolins after being trafficked into Southern China, consistent with the respiratory distress they exhibit (Liu et al 2019 ;Xiao et al 2020) and the lack of evidence of infection of Sunda pangolins in Malaysia (Lee et al 2020) .…”
mentioning
confidence: 84%
“…The most common routes involve moving the animals from Southeast Asia (Myanmar, Malaysia, Laos, Indonesia, Vietnam) to Guangxi, Guangdong, and Yunnan. The most likely scenario is that these Sarbecoviruses infected the pangolins after being trafficked into Southern China, consistent with the respiratory distress they exhibit (Liu et al 2019 ;Xiao et al 2020) and the lack of evidence of infection of Sunda pangolins in Malaysia (Lee et al 2020) .…”
mentioning
confidence: 84%
“…Moreover, pangolins are solitary animals, and infection by these pangolin CoVs is lethal for most pangolins 9 , suggesting that these pangolin CoVs might not be native to pangolins. Recent studies on 334 Sunda pangolins did not find any CoVs or other potential zoonotic viruses in these animals 38 , further supporting that pangolins might not be reservoir hosts for these pangolin CoVs. Where, when, and how these pangolins acquired these CoVs remain elusive.…”
Section: Discussionmentioning
confidence: 79%
“…14 A recent study on wild or recently captured Malayan pangolins has shown no presence of CoVs. 15 Palm civets infected with SARS-CoV 16 similarly showed signs of illness and respiratory distress, suggestive as a role as an intermediate host but unlikely to be a natural reservoir.…”
Section: Conflicmentioning
confidence: 99%